Morphology and Immunoexpression of Selenoproteins in Term Placenta of Alpaca (Vicugna pacos) from the Peruvian Andes - Miluska Beatriz Navarrete Zamora; Francisco Acuña; Mônica Duarte da Silva; Thamires Santos-Silva; Matheus Henrique Herminio Garcia; Rodrigo da Silva Nunes Barreto; Alberto Sato Sato; Claudio Gustavo Barbeito; Maria Angelica Miglino (Biology)
South American camelids inhabit high-altitude environments characterized by hypoxia, influencing embryonic, fetal, and placental development. This study examined the term placenta morphology of alpacas (Vicugna pacos, N = 12) and the immunoexpression of antioxidant selenoproteins (SP). We hypothesize that the placenta of alpacas, adapted to high altitudes, has characteristics with other species also adapted to altitude. Placentas were paraffin-embedded, sectioned (3–5 µm), stained with hematoxylin–eosin (H&E), Masson’s trichrome, and picrosirius red, and analyzed via light and polarized light microscopy. The chorion showed simple cuboidal epithelium with binucleated cells, a subepithelial mesenchyme rich in blood capillaries (area: 124.90 ± 9.82 µm2), and type III collagen fibers. The chorionic villi measured 2740.22 ± 132.75 µm. The allantois contained a simple columnar epithelium and mesenchyme with type I collagen fibers. Immunohistochemistry localized SP-N, SP-P, Dio-3, and GPx-3 in the blood capillaries and mesenchymal tissue of the chorion but not in the allantois. These findings were compared to human and sheep placentas from different altitudes due to a lack of camelid data at low levels. The morphological features resembled adaptations to hypoxia observed in other species. This preliminary study suggests a potential role for selenoproteins in hypoxia adaptation, providing a basis for future functional studies.